Sistema tutorial inteligente para la enseñanza y evaluación en niños de preescolar. - Ojeda Azuero, Katherine del Carmen, Wilson Eduardo Vélez Cañar (2016)
Every day the technology is evolving rapidly, that is why there is now much dependence and necessity of systems to make a work more efficient and also get better results. In education, for teaching-learning intelligent tutoring systems have been great contributions for students and teachers in order to improve the process and thereby achieve quality and excellence in education. This project includes the development of an intelligent tutoring system for teaching and evaluation in preschool, in order to provide a tool that will improve the teaching method applied in the vocal theme, colors and numbers interactively, based on teaching methods that best suit the learning style of children. For the development of the titling work, a stage of analysis and requirements elicitation was performed, for which was used several collection techniques for information applied to Preschool education establishments. The system is developed under the Java programming language, and also used the HTML5, CSS3, JavaScript technologies, implemented as manager MySql Database, This system is going to work on a web platform and mobile devices. For the implementation of the intelligent part of the system in this case the development of the Artificial Neural Network was used the Weka library as this works with java, the neural network will take the input data (score, Time, Error) after each session of the student, is going to be processed and classified giving as a result a suggestion that will reveal what the student has to improve in the next session and in that way determine the level of learning through graphs of results. In the section of results is detailed the methodology used for system construction that In this case was XP (Extreme programming), here is described the system requirements , use case diagrams, interface design , etc., Including the integration and development more with detail of the Supervised Artificial Neural Network with Which the project of titling work concludes satisfactorily. As final part of the Project would have the discussion Which Explains How met each of the Objectives. Also presents the Conclusions and recommendations Obtained During the development of intelligent tutoring system, notably, the present project can be used in different establishments Preschool As well as in homes for children can interactively learn and Improve teaching method traditionally used.